Immunophenotype evaluation of Non-Hodgkin’s lymphomas - Sheikhpour, Robab (Med J Islam Repub Iran, 2017)
Background: Non-Hodgkin’s lymphoma (NHLs) is known as a heterogeneous group of malignant lymphoproliferative disorders. NHLs are classified into B cell and T cell types. Immunophenotypical assessment of the biopsy specimens can help diagnose NHLs. Methods: In this study, 77 patients with B cell and T cell lymphoma were selected from Shahid Sadoghi hospital during 2010 to 2013. Immunohistochemical method was used to detect biomarkers like CD2, CD3, CD20, and CD45. Results: In this study, 67 patients (87.01 %) had B cell lymphoma. Moreover, the most primary tissues in B cell group were lymph node and stomach, followed by bone marrow and neck. Positive co-expression of CD45 and CD20 was found in 61 patients (91.04%) with B cell lymphoma. However, 10 patients (12.98%) had T cell lymphoma, and the most primary tissue in T cell lymphoma group was the skin. Moreover, CD3 expression was seen in all patients with T cell lymphoma. Conclusion: This study confirmed the main role of immunohistochemistry method in classifying and diagnosing NHLs. Moreover, the difference in CD marker expression and age in patients with B cell and T cell lymphoma, compared to other studies may be due to geographic area and genetic and ethnic differences.